Successful surgical management of post-traumatic cirsoid aneurysm - Sajikumar, N. R.; Mathai, Jolhf Koshy; Harold, Dimmy (International Surgery Journal, 2017)
Cirsoid aneurysms are rare arteriovenous malformations (AVM) of the scalp and extremities. They are commonly congenital but post-traumatic cirsoid aneurysms have also been reported. Clinical features include- gradually increasing swelling, pulsatile mass, bruit, headache and tinnitus. Post-traumatic aneurysms of the scalp are uncommon. We report a case with successful surgical excision of scalp AVM.